2019
DOI: 10.1093/cdn/nzz048.p11-076-19
|View full text |Cite
|
Sign up to set email alerts
|

Stool pH and Short/Branched Chain Fatty Acids in Infants Receiving Extensively Hydrolyzed Formula, Amino Acid Formula, or Human Milk Through Two Months of Age (P11-076-19)

Abstract: Objectives Infant feeding influences early development of the gut microbiome, colonization pattern, and community structure. Metabolites, including short- and branched-chain fatty acids (S/BCFA) (e.g., butyrate, propionate), produced by colonic bacteria serve as signaling molecules, influence immunity, and reduce luminal pH in the gastrointestinal environment. The objective of this study was to evaluate stool S/BCFA and pH in infants fed with different sources of dietary protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The higher levels of propionate and butyrate acids showed in formula-fed are in agreement with some of the rst studies investigating this relationship [57]. With independence of breastfeeding, it is possible that, undigested proteins and amino acids can pass into the large intestine, being fermented by certain bacteria producing different bacterial metabolites, such as SCFAs [58,59]. Consistent with this nding, we observed that infants belonging to cluster I (those with higher excretion of SCFAs) had signi cantly higher total protein intake than cluster II at 90 and 180 days (10.36 g/day vs. 8.75 g/day and 15.17 vs. 13.47, respectively) (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…The higher levels of propionate and butyrate acids showed in formula-fed are in agreement with some of the rst studies investigating this relationship [57]. With independence of breastfeeding, it is possible that, undigested proteins and amino acids can pass into the large intestine, being fermented by certain bacteria producing different bacterial metabolites, such as SCFAs [58,59]. Consistent with this nding, we observed that infants belonging to cluster I (those with higher excretion of SCFAs) had signi cantly higher total protein intake than cluster II at 90 and 180 days (10.36 g/day vs. 8.75 g/day and 15.17 vs. 13.47, respectively) (data not shown).…”
Section: Discussionsupporting
confidence: 82%
“…with the intensity of the increases being donor-dependent ( Figure 1A,B). Branched SCFAs (isobutyrate, isovalerate and isocaproate) were not detected (data not shown) as expected in preweaning infants [67], while effects on propionate and butyrate production were minor and donor-dependent ( Figure A1A,B).…”
Section: Bmos Significantly Modulated Gut Microbial Activity and Compsupporting
confidence: 63%